The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.
We use the property of square roots that says the square root of (ab)=square root (a) multiplied by square root of b So square root (4x)=square root (4) mutiplies by square root of x =2(square root (x)) 2sqrt(x)
√3 x √27 = 9
The square root of x has two answers. It's either x (which is +x), or it's -x. If we take x times x, the answer is x2. If we take -x times -x, the answer is also x2.
The square root of 8 is 2 times the square root of 2 sqrt(8) = 2 x sqrt(2)
Its the square root of 2 times x Ambiguous. More clear is x times square root of 2
It depends entirely on the value of x.
(√4x^2)(√36x)=2x(6√x)=12x√x
2 x √3 = 3.464 (rounded)
X = any number you like. You see, in order to solve for x, one would have to know what those two things equaled. For instance, what if x = zero? The square root of 2 times zero multiplied by the square root of 50 times zero, is going to be zero.
The question is ambiguous. Do you mean √(24*x4) or √24*x4? √(3x) or √3*x? The answer to √(24*x4) / √(3x) = (8x3) = 2x*√(2x)
The equation "1/2x^2 = x" can be rewritten as "x^2 - 2x = 0" by multiplying both sides by 2 to eliminate the fraction. This equation can be factored as x(x-2) = 0, leading to solutions x=0 and x=2. Therefore, the values of x that satisfy the original equation are x=0 and x=2.
The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.
The polynomial is not factorable with rational numbers. If you want to use irrational numbers it would be x minus the square root of 2 times x plus the square root of 2.
As stated, the question does not make sense: x square root of 4 is x2 or 2x, as it is more conventionally written. There is no term for 2x in the expansion of x - 3*sqrt(7)
square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them
2x square root 6x y squared